Methodological approaches of health policy analysis in developing countries - Suliman, Qudsiah; Kang, Chia Yee; A. F., Fatimah; Zainal Abidin, Zamzaireen; Che Ishak, Natalia; Kharie, Mohamad Fadli; Ghebreab, Luam Ghebrehiwot; Abdalrheem, Tasneem Abdalgfar Alawad; M., Fateh; Juni, Muhamad Hanafiah (Community Health Society Malaysia, 2017)
Background: Policy analysis is the process of identifying problem, defining and analyzing process, qualitative and quantitative analysis, evaluation, recommendation, aiming to inform choices leading to an improved healthcare system. In developing country, the analysis of health policy has been given limited attention. As health is influenced by many external sectors and the dynamic in healthcare system, it is a challenging task in health policies analyses. The aim of this manuscript is focusing on health policy analysis in developing countries using the methodological approaches of theories, frameworks and study designs. Materials and Methods: Scoping systematic review was used for this manuscript writing. Recent ten year articles were searched from public domains with keywords of “health policy”, “developing countries”, “theory”, “framework” and “study design”. A total of 18 articles were finalized to be included, six for each methodological approaches. Result: Theories such as Group Theory, Multiple Implementation Theory, and Kingdon Multiple Stream Theory are among the commonest theories used in policy analysis. In translating framework approach into health policy analysis, Policy Triangle Framework, 3-i Framework (idea, interest and institution) and Social Determinant of Health Framework are also widely used. The mixed method of qualitative and secondary data based quantitative; and cross-country comparative case study are frequently adopted for study design approach. Conclusion: A common methodological approaches in health policy analyses were used an established theoretical approach, a feasible approach of study design and a comprehensive framework. However evidenced based approach is also use as a fundamental approach in health policy analysis especially in developing countries with limited resources.